Impunity from accountability for election crimes : analysis of crimes committed by Zimbabwe authorities and ZANU-PF militia during the 2008 election - Hansungule, Michelo (University of Pretoria, 2019)
Mini Dissertation (MPhil)--University of Pretoria, 2018.